Harnessing the natural intelligence of wood to improve passive ventilation in buildings - Fabio Bianconi; Marco Filippucci; Giulia Pelliccia; David Correa (Techne)
Wood actively equalises its moisture content in relation to its surrounding environment. Technical applications that can harness this characteristic can have a great impact in the improvement of indoor hygrometric comfort. So far few applications have made use of this unique property. The natural hygroscopic intelligence of wood can lead to the development of a new technology capable of ensuring improved indoor comfort. The natural material can thus be engineered by creating responsive composites made from wood waste and transformed through 4D printing. The biomimetic actuators studied in this paper are aimed at linking the transformation of form into environmental control functionality applied to building comfort in adaptive and passive solutions.